دور مبادئ إدارة الجودة الشاملة في تقويم جودة التعليم العالي من وجهة نظر أعضاء الهيئة التدريسية(دراسة ميدانية على أعضاء الهيئة التدريسية في كلية العلوم بجامعة تشرين) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت الدراسة إلى الآتي: بيان دور إدارة الجودة الشاملة في تقويم جودة التعليم في جامعة تشرين، دراسة العلاقة بين إدارة الجودة الشاملة ومدخلات، عمليات، مخرجات التعليم في جامعة تشرين، بيان دور إدارة الجودة الشاملة في تطوير العملية التعليمية في جامعة تشرين. تم استخدام المنهج الوصفي التحليلي لقياس دور إدارة الجودة الشاملة في تقويم جودة التعليم بجامعة تشرين من وجهة نظر أعضاء الهيئة التدريسية في كلية العلوم، تم تصميم وتوزيع استبانة على أعضاء الهيئة التدريسية في كلية العلوم، كما تم دراسة وتحليل البيانات باستخدام برنامج spss ، وبعد التحليل توصلت الدراسة إلى مجموعة من النتائج من أهمها الآتي: عدم وجود اهتمام كافي بمبادئ إدارة الجودة الشاملة،  وجود العديد من الصعوبات المتعلقة بإدارة الجودة الشاملة من أهمها(التحسين، التدريب، عدم قياس الرضا)، انخفاض جودة مدخلات ومخرجات وعمليات الموقف التعليمي في كلية العلوم بجامعة تشرين من وجهة نظر أعضاء الهيئة التعليمية. The study aimed at the following: The role of TQM in evaluating the quality of education at Tishreen University, the study of the relationship between TQM and inputs, processes and outputs of education in Tishreen University, the role of TQM in developing the educational process in Tishreen University. The analytical descriptive approach was used to measure the role of TQM in evaluating the quality of education at Tishreen University. From the point of view of faculty members in the Faculty of Science, a questionnaire was designed and distributed to the faculty members of the Faculty of Science. Data analysis and analysis were also carried out using the SPSS program. After the analysis, the study reached a number of results, the most important being the following: The lack of sufficient interest in the principles of TQM, the existence of many difficulties related to TQM (improvement, training, lack of satisfaction measurement), low quality of inputs and outputs and processes of the educational situation in Tishreen University from the point of view of members of the faculty of the Faculty of Science.